2016
DOI: 10.1097/igc.0000000000000741
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Use of Pretreatment Hematologic Parameters in Patients Receiving Definitive Chemoradiotherapy for Cervical Cancer

Abstract: Pretreatment NLR and PLR were associated with larger tumors, lymph node metastasis, and poorer therapeutic responses to definitive ChRT. By multivariate analysis, pretreatment NLR and lymph node metastasis were found independently predictive of OS and PFS, whereas patients' age was significantly predictive of OS only. In patients with advanced cervical cancer, NLR is a potential biomarker, serving to guide systemic therapy and predict treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 32 publications
0
52
5
Order By: Relevance
“…These studies came from China [25, 27, 29, 30, 32–36], Korea [37], Japan [26, 31], and Turkey [28], respectively. Twelve articles reported the outcomes of overall survival (OS) [25–33, 35–37], and 10 studies presented progression-free survival (PFS) as primary outcome [2628, 31–37]. The hazard ratios (HRs) and the corresponding 95% confidence intervals (CIs) were obtained by multivariate analyses in 8 studies and through univariate or Kaplan–Meier curves in 5 studies [2527, 34, 36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies came from China [25, 27, 29, 30, 32–36], Korea [37], Japan [26, 31], and Turkey [28], respectively. Twelve articles reported the outcomes of overall survival (OS) [25–33, 35–37], and 10 studies presented progression-free survival (PFS) as primary outcome [2628, 31–37]. The hazard ratios (HRs) and the corresponding 95% confidence intervals (CIs) were obtained by multivariate analyses in 8 studies and through univariate or Kaplan–Meier curves in 5 studies [2527, 34, 36].…”
Section: Resultsmentioning
confidence: 99%
“…The hazard ratios (HRs) and the corresponding 95% confidence intervals (CIs) were obtained by multivariate analyses in 8 studies and through univariate or Kaplan–Meier curves in 5 studies [2527, 34, 36]. Five studies included CC patients with all disease stages (Stages I–IV) [26, 28, 31, 33, 37], seven studies recruited patients with Stages I–II [25, 29, 30, 32, 34–36] and only one study reported the data of CC patients with Stages II–III [27]. The primary treatments were extremely various among the 13 included studies, including concurrent chemoradiotherapy (CCRT) [2628], surgery with neoadjuvant chemotherapy (NACT) [30, 36], surgery with adjuvant therapy (AT) [25, 29, 32, 35], surgery alone [34], radiotherapy or CCRT [31, 33], and mixed treatments [37].…”
Section: Resultsmentioning
confidence: 99%
“…Lymphocytes are involved at various steps of host response to cancer, and may modulate response to treatment [14,15]. Lymphopenia and decreased ratio of lymphocytes to neutrocytes or platelets might be prognostic factor in survival for various cancer types [16][17][18][19]. Moreover pretreatment lymphopenia was proposed to predict survival and early death after chemotherapy for breast cancer, lymphomas and sarcomas [20,21].…”
Section: Rt and Immunitymentioning
confidence: 99%
“…Among these pretreatment blood parameters, the peripheral neutrophil-lymphocyte ratio (NLR), calculated as the absolute neutrophil count (ANC) divided by the absolute lymphocyte count (ALC), is regarded as a simple and effective marker of inflammation 23 - 25 that has been consistently reported to have an independent prognostic value in various tumors 21 , 22 , 26 . An increased NLR was associated with advanced stages of cervical neoplasia 27 , 28 , and patients with a higher histologic grade of CIN showed higher numbers of total leukocytes 29 .…”
Section: Introductionmentioning
confidence: 99%